PENAMBAHAN ABU TEMPURUNG KELAPA TERHADAP KUAT TEKAN PAVING BLOCK - Wahyu Saputra; Prihantono; Bachtiar, Gina (Jurnal Pendidikan Teknik dan Vokasional, 2020)
The study aims to find out the influence of the use of grey add coconut shell on paving block against the requirement of quality set out in SNI 03-0691-1996 which includes the nature, size, moisture absorption and powerful press. Ash is produced from coconut shell burning at a temperature of 8000C. The proportion used is 0%, 5%, 6%, 7% and 8% of the cement weight. The study was conducted in Laboratory Test Materials Research Department Civil Engineering State University Of Jakarta. The time the study was conducted in August 2016 with experimental methods in accordance with Indonesia's National Standard (SNI). Making a test done at the factory PD.MAJU PUTRI, Highway 45, 1 No Kavling Cipayung Jak-Team. This type of paving block used was paving block brick-shaped with dimensions of up to 21cm x 10,5cm x 8cm, with a comparison of cement and sand 1:3 by the number of samples as much as 40 fruit. The results of this research to powerful press time soaking 14 and 28 days. The Group of 14 days 0%, 5%, 7